Mucinous cystadenoma of both ovaries and appendix: a case report - Agrawal, Sujan N.; Goyal, Manisha; Prasad, Sanjay (International Surgery Journal, 2024)
Epithelial neoplasm of ovaries is common and almost 40% of them are benign. Cystadenoma of ovary is the commonest epithelial neoplasm. They can be serous or mucinous. They arise from the surface epithelium of ovary, some of them may have germ cell origin. They are multilocular. 80% of ovarian mucinous cyst are benign cystadenoma. They are unilateral in 95% of cases. In this case presentation, it was bilateral and appendix was also showing mucinous cystic degeneration. The mucinous cystadenoma of the appendix is the most common mucinous cyst of the appendix, but the definite diagnosis is made at the time of surgical intervention only. The confirmation is reached by histopathology examination of specimen. This interesting case report is that of a giant bilateral ovarian mucinous cystadenoma of ovary along with the cystic degeneration of appendix. This is a rare case presentation scenario where bilateral giant cyst is found along with same pathology in appendix.